Front Cover: Versatile Electrochemical Oxidative C(sp2)−H Bond Selenylation of Resveratrol (Eur. J. Org. Chem. 31/2021). Issue 31 (9th August 2021) - Lazzaris, Maika J.; Martins, Guilherme M.; Xavier, Fernando R.; Braga, Antonio L.; Mendes, Samuel R.
Abstract : The Front Cover was inspired by the painting on the Sistine Chapel ceiling, made by Michelangelo. Here we represent the creation of new resveratrol derivatives via galvanostatic electrolysis in an undivided cell. An environmentally benign procedure was developed for the electrochemical oxidative mono‐ and bis‐selenylation of the C(sp2)‐H bond, under oxidant‐, base‐, and transition metal‐free conditions, in an open system at room temperature. More information can be found in the Communication by S. R. Mendes et al.